A Simplified Design and Modeling of Boost Converter for Photovoltaic Sytem - Arjyadhara Pradhan; Bhagabat Panda (Institute of Advanced Engineering and Science, 2018)
The Photovoltaic standalone system is gaining its high importance mostly for rural application like pv water pumping, solar lighting, battery charging etc.Considering environmental effects and scarcity of fossil fuel the trend has developed towards the use of more and more renewable energy.In this paper a basic circuit of boost converter is designed in MATLAB/Simulink with constant dc source voltage. However a comparative study has also been done for the converter connected with pv system directly with the converter connected with mppt tracking technique. Perturb and Observance (P&O) algorithm is implemented for providing the necessary duty pulse and makes the system operate at maximum power point.The boost converter connected with PV system without mppt operates at any other point other then the maximum power point and hence the output voltage decreases.But with mppt the proposed system performs better.